2017
DOI: 10.21608/ejm.2017.677.1013
|View full text |Cite
|
Sign up to set email alerts
|

Study the Association of Helicobacter pylori and some of Hepatitis C Virus Patients in Egypt

Abstract: B OTH hepatitis C virus and Helicobacter pylori infections are commonly found in Egypt. Correlation among Helicobacter pylori and HCV has been assisted. This work aim was to research H. pylori DNA inside the liver tissue of Egyptian suffers with persistent hepatitis C and find the relation among HP invasion and HCV.This prospective study was conducted with 49 participants. Helicobacter pylori Standard Kit (H.pylori) genome is designed for the in vitro H.pylori genomes from liver tissues patients with chronic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In the current study, liver cirrhosis at patient with concomitant H. pylori and chronic HCV infections showed a high percentage compared to those patients with chronic HCV mono-infection. Several previous reports revealed a strong association between H. pylori infection and the progression of liver injuries such as cirrhosis and fibrosis among HCV infected patients [28,34,35,37,38,40,41].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the current study, liver cirrhosis at patient with concomitant H. pylori and chronic HCV infections showed a high percentage compared to those patients with chronic HCV mono-infection. Several previous reports revealed a strong association between H. pylori infection and the progression of liver injuries such as cirrhosis and fibrosis among HCV infected patients [28,34,35,37,38,40,41].…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, in the current study, biochemical assessment and HCV RNA load at patient with concomitant H. pylori infection and chronic HCV infection was similar to patients with chronic HCV mono-infection. Several reports demonstrated that there was no statistical difference between ages, gender, liver function tests, AFP levels or viral load in the prevalence of H. pylori in HCV infected patients [37,40,41].…”
Section: Discussionmentioning
confidence: 99%